Artificial Neural Network: Artificial Neural Network Approach to Predict the Elastic Modulus from Dynamic Mechanical Analysis Results (Adv. Theory Simul. 4/2019). Issue 4 (4th April 2019) - Xu, Xianbo; Gupta, Nikhil
Abstract : In article number1800131, Xianbo Xu and Nikhil Gupta report on combining an artificial neural network and viscoelastic theory to recover the elastic modulus of graphene‐reinforced composites from dynamic mechanical analysis results. Instead of conducting numerous tensile tests, the method can predict the elastic modulus over a range of strain rates and temperatures from a single specimen.